Postoperative pain and pain management following selective dorsal rhizotomy - Mohamed E Abdel-Latif; Jennifer Lewis; Nadia Badawi; Simon Paget; Isabel G Adams; Ramanie Jayaweera (BMJ Publishing Group, 2024)
Background Selective dorsal rhizotomy (SDR) is a neurosurgical procedure that reduces lower limb spasticity, performed in some children with spastic diplegic cerebral palsy. Effective pain management after SDR is essential for early rehabilitation. This study aimed to describe the anaesthetic and early pain management, pain and adverse events in children following SDR.Methods This was a retrospective cohort study. Participants were all children who underwent SDR at a single Australian tertiary hospital between 2010 and 2020. Electronic medical records of all children identified were reviewed. Data collected included demographic and clinical data (pain scores, key clinical outcomes, adverse events and side effects) and medications used during anaesthesia and postoperative recovery.Results 22 children (n=8, 36% female) had SDR. The mean (SD) age at surgery was 6 years and 6 months (1 year and 4 months). Common intraoperative medications used were remifentanil (100%), ketamine (95%), paracetamol (91%) and sevoflurane (86%). Postoperatively, all children were prescribed opioid nurse-controlled analgesia (morphine, 36%; fentanyl, 36%; and oxycodone, 18%) and concomitant ketamine infusion. Opioid doses were maximal on the day after surgery. The mean (SD) daily average pain score (Wong-Baker FACES scale) on the day after surgery was 1.4 (0.9), decreasing to 1.0 (0.5) on postoperative day 6 (POD6). Children first attended the physiotherapy gym on median day 7 (POD8, range 7-8). Most children experienced mild side effects or adverse events that were managed conservatively. Common side effects included constipation (n=19), nausea and vomiting (n=18), and pruritus (n=14). No patient required return to theatre, ICU admission or prolonged inpatient stay.Conclusions Most children achieve good pain management following SDR with opioid and ketamine infusions. Adverse events, while common, are typically mild and managed with medication or therapy. This information can be used as a baseline to improve postoperative care and to support families' understanding of SDR before surgery.